Factors Causing Contraceptive Acceptors Drop Out - mufdlilah, mufdlilah; Aryekti, Kanthi (Kesmas, 2018)
Family planning program has a very strategic, comprehensive and fundamental meaning in creating a healthy and prosperous Indonesian human being. However, recently the incidence of drop out is quite high for several reasons. This study was conducted to determine the influential factors that cause acceptors to drop out. It is descriptive research. The populations in the study were contraceptive acceptors who dropped out for 3 consecutive months, and not being pregnant. The numbers of sample were 100 people. The data collection employed closed and open questionnaires; data presented in descriptive form. Influential factors of drop out contraceptive acceptors due to side effects were 38%, wanting children 18%, others (changing the method/ expired) 14%, without husband support in using contraception 22%, and others 22%. The period of using contraception after dropout 34% (3-10 years); express unlimited time (one day later) and unwilling to use contraception anymore after dropping out 23%. It is suggested that health professionals can increase the handling of family planning side effects, improve counseling, information and education related to the choice of short term non hormonal contraceptive devices related to the selection of contraceptives for pre-menopausal age so that the decision making can be taken more appropriately, increase the competence of health professionals, increasing husband support, improving mentoring and monitoring acceptors who have dropped put to use contraceptives again willingly.